Two new synonyms in the dung beetle genus Parachorius (Coleoptera: Scarabaeidae: Scarabaeinae) from the Oriental Region - Tarasov, Sergei (Zootaxa, 2018)
The dung beetle genus Parachorius Harold, 1873 (= Cassolus Sharp, 1875) belongs to the monotypic tribe Parachoriini Tarasov, 2017 and includes 19 species from the Oriental and southeastern Palaearctic Regions (Tarasov 2017). Two recent studies (Ochi et al. 2017a, b) described two new species of this genus from Laos and Sumatra. The investigation of detailed descriptions and illustrations from those studies and their assessment in the light of the recent revision of Parachorius (Tarasov 2017) revealed that those new species are synonyms of earlier described ones: P. javanus (Boucomont, 1914) = P. singgalangensis Ochi, Kon & Hartini, 2017, new synonymy, and P. fukiensis (Balthasar, 1960) = C. laosensis Ochi, Kon & Higurashi, 2017, new synonymy. Unfortunately, this oversight happened because the authors of those new species did not check the type material of already described taxa.